lnx-ln(x+4)=2

Simple and best practice solution for lnx-ln(x+4)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for lnx-ln(x+4)=2 equation:


Simplifying
lnx + -1ln(x + 4) = 2

Reorder the terms:
lnx + -1ln(4 + x) = 2
lnx + (4 * -1ln + x * -1ln) = 2
lnx + (-4ln + -1lnx) = 2

Reorder the terms:
-4ln + lnx + -1lnx = 2

Combine like terms: lnx + -1lnx = 0
-4ln + 0 = 2
-4ln = 2

Solving
-4ln = 2

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Divide each side by '-4n'.
l = -0.5n-1

Simplifying
l = -0.5n-1

See similar equations:

| 5x-5x=-24 | | 4n^2-48n+144=0 | | -(n+3)=-3+3n | | 7x+65=2x+45 | | (n-5)(8n-7)=0 | | x=1.3 | | 13x-41=180 | | 7(4y-5)+3(4y+6)= | | 8n^2-80n+200=0 | | -x/3=x/3+52 | | 5x/7=x/7+644 | | (7p-9)(9p+5)=0 | | 60=12+6(n-1) | | 2x(x-4)=-14x+8 | | 6x+27+3x+54=180 | | -17-5p=5(2+4p)+2p | | -58.75-x/8=7x/8+191.25 | | 14b-13b+3b=20 | | u(6u-7)=0 | | 4ln(7x)=16 | | -17-5p=5(2+4)+2p | | 3x^3-2x^2-12x+18=0 | | 6w+5w-9w=12 | | 5y(y+2)=0 | | 2tanx+7=3 | | 6+2x-5=6-3(2x-1) | | 10h-8h+h-3h+h=7 | | 5+3(x+4)=-(2x-1)-9 | | log[4](13*7)= | | 5r^2-10r-15=0 | | 2x^3+13x=8x^2 | | -17-55p=5(2+4p)+2p |

Equations solver categories